Selectivity and affinity of triplex-forming oligonucleotides containing 2'-aminoethoxy-5-(3-aminoprop-1-ynyl)uridine for recognizing AT base pairs in duplex DNA. - Osborne, S; Powers, V; Rusling, D; Lack, O; Fox, K; Brown, T (2004)
We have used DNase I footprinting, fluorescence and ultraviolet (UV) melting experiments and circular dichroism to demonstrate that, in the parallel triplex binding motif, 2'-aminoethoxy-5-(3-aminoprop-1-ynyl)uridine (bis-amino-U, BAU) has very high affinity for AT relative to all other Watson-Crick base pairs in DNA. Complexes containing two or more substitutions with this nucleotide analogue are stable at pH 7.0, even though they contain several C.GC base triplets. These modified triplex-forming oligonucleotides retain exquisite sequence specificity, with enhanced discrimination against YR base pairs (especially CG). These properties make BAU a useful base analogue for the sequence-specific creation of stable triple helices at pH 7.0.